A new species of termite, Neotermes Holmgren (Blattodea: Isoptera: Kalotermitidae) from India with a note on morphometry of Neotermes nilamburensis Thakur. (2nd October 2022) - Ranjith, Mannarakkoth; Kalleshwaraswamy, Chicknayakanahalli M.; Meghana, Kolavalli J.; Singh, Sudhir; Santhrupthi, Basrur; Karthik, Chikkabidare M.
ABSTRACT: Southern India is unique by many endemic species of flora and fauna especially in the Western Ghats, a global biodiversity hotspot. Neotermes Holmgren is widely distributed genus of the family Kalotermitidae. A new species of kalotermitid termite, Neotermes viraktamathi sp. nov . is here described from Karnataka part of Western Ghats. The species was collected from a dead branch of a live tree. Additionally, for the first time, 16S rRNA sequence of an Indian Neotermes is provided. A note on variation observed in morphometrics of an endemic species, Neotermes nilamburensis Thakur is also discussed. http://www.zoobank.org/urn:lsid:zoobank.org:pub:C1B5291B-65E4-4C91-8E27-81F7CC875CB6